The Influence of Reward and Organizational Culture on Employee Performance through Work Motivation on PT Pos Indonesia Surabaya Main Branch - Firdaus Rezando Rohman; Endang Iryanti (International Journal of Economics (IJEC), 2023)
In the current era of global competition, the determinant of a company's success is the quality of human resources in the company. To be able to realize the company's vision and mission, PT Pos Indonesia Surabaya Main Branch must have good and quality human resources to be able to play an active role in achieving company goals. There is a decrease in the achievement of company targets, indicating that the performance of employees at PT Pos Indonesia Surabaya Main Branch has decreased. With a decrease in employee performance, further research is needed which aims to determine the effect of Rewards and Organizational Culture on Employee Performance through Work Motivation at PT Pos Indonesia Main Branch Surabaya. This research is expected to be useful as material for performance evaluation and management considerations to improve the quality of employee performance. This study used a quantitative research method with a purposive sampling technique using the slovin formula. The population and sample in this study were 55 employees working at PT Pos Indonesia. The data in this study includes primary and secondary data. Primary data obtained from company reports, primary data from questionnaire results. This study uses the smartPLS 3.0 test tool, the results of which prove that Rewards have an effect on Employee Performance, Organizational Culture has an impact on Employee Performance, Motivation can be a mediationReward on Employee Performance, and Motivation can mediate Organizational Culture on Employee Performance at PT Pos Indonesia Surabaya Main Branch.